1999
DOI: 10.1021/cm9900352
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Metal Deposition onto Functionalized Polystyrene Microspheres

Abstract: Three different methods are described for uniformly anchoring metal colloids (Pt, Pd, and Au) onto the surface of polystyrene microspheres (PSMS). The first method we have employed is electrostatic deposition of preformed anionic colloidal particles onto a polycationic surface. In this method the functional groups on the surfaces of the microspheres (amine or carboxylic acid) are used to give the surface a net charge. These ionic spheres were then treated with polyelectrolytes of the opposite charge, which uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
185
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(186 citation statements)
references
References 40 publications
(33 reference statements)
1
185
0
Order By: Relevance
“…Dokoutchaev et al recently reported the alternating assembly of metal nano-sized particles and oppositely charged polyelectrolyte onto polystyrene microspheres. [64] In that work, [64] low gold nanoparticle coverage and non-uniform coatings were obtained, although the nanoparticle loading was increased by repeated depositions of nanoparticle and polyelectrolyte in the LbL manner. Using the same strategy, Caruso et al demonstrated the step-wise formation of regular nanoparticle layers on colloidal particles.…”
Section: Controlled Assembly Of Preformed Nanoparticlesmentioning
confidence: 97%
See 2 more Smart Citations
“…Dokoutchaev et al recently reported the alternating assembly of metal nano-sized particles and oppositely charged polyelectrolyte onto polystyrene microspheres. [64] In that work, [64] low gold nanoparticle coverage and non-uniform coatings were obtained, although the nanoparticle loading was increased by repeated depositions of nanoparticle and polyelectrolyte in the LbL manner. Using the same strategy, Caruso et al demonstrated the step-wise formation of regular nanoparticle layers on colloidal particles.…”
Section: Controlled Assembly Of Preformed Nanoparticlesmentioning
confidence: 97%
“…[80] Using a similar method, Dokoutchaev et al formed metal particles of 2±4 nm diameter on polystyrene microspheres by depositing a precursor metal (palladium) oxide or hydroxide onto the spheres, followed by reduction to give fine metal particles on the surface. [64] The synthesis of polymer-coated microspheres with silver colloids on their surface using free radical chemistry has also been reported. [81] The metal salt and organic monomers are mixed together in solution.…”
Section: Precipitation and Surface Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such materials provide a new class of supramolecular building blocks and can "exhibit unusual, possibly unique, properties which cannot be obtained simply by co-mixing polymer and inorganic particles." (Barthet et al, 1999) In comparison with the recently reported methods to synthesize core-shell composite particles, for example, post-surface-reactio (Ding et al, 2004;Lynch et al, 2005), electrostatic deposition (Dokoutchaev et al, 1999), and layer-by-layer self-assembly (Caruso, 2001;Caruso et al, 1999;Caruso et al, 2001), we synthesize core-shell composite nanoparticles through a novel Pickering emulsion polymerization route (Ma and Dai, 2009;Ma et al, 2010). Figure 1 illustrates the polymerization route and its comparison with the conventional emulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies on metal nanoparticles (MNPs) are continuously increasing because of their unusual properties compared to bulk metals and potential applications in electrical, optical, magnetic, catalytic, and chemical/ biochemical sensing areas [12][13][14]. MNPs-based composites have been prepared through incorporation of them into silica or metal oxide surfaces [15], polymer micelles [16], and microspheres [17].…”
Section: Introductionmentioning
confidence: 99%